How did educational institutions respond to students with special needs during COVID-19: considerations for policy? - Gómez-Domínguez, Valentina; Gómez-Domínguez, MaríaTeresa; Navarro-Mateu, Diego; Tébar-Yébana, Susana (Frontiers in Education, 2024)
This bibliometric study analyzes the scientific production on the educational response of institutions to families with children with special educational needs (SEN) during the COVID-19 pandemic. The research identifies emerging trends and distinctive characteristics, providing a foundation for improving strategies in schools. The analysis reveals an increase in publications from 2020 to 2023, peaking at 24 articles in 2022. A total of 246 researchers participated, with Castro-Kemp S and McIntyre LL standing out for their productivity and citations. Institutions such as UCL and the University of Oregon led in publications, while the University of California, Santa Barbara, topped the citations. In terms of scientific production, the United States had the most articles, followed by the United Kingdom and Spain. However, the United Kingdom led in global citations, indicating a high level of interest in the topic. The main journals in this field include Frontiers in Education and Education Science. Twelve collaboration networks among authors were identified, with a primary network of seven closely collaborating researchers. The pandemic exacerbated pre-existing difficulties in the education of children with SEN, increasing stress and emotional burden on parents. The transition to home education and the lack of adapted resources presented significant challenges. However, some strategies, such as dialogic literary gatherings and collaboration between schools and families, proved effective in mitigating negative impacts. The study underscores the need for inclusive public policies that address disparities in educational support and prioritize the psychological well-being of children with SEN. It recommends a proactive and equitable approach in school psychology training and educational practice. In conclusion, this analysis provides a solid foundation for future research and improvements in schools, promoting an inclusive and resilient educational environment.